New dimensions to sewage water use in crop production - Neeraja, C R; Patel, M V (Indian Farming, 2018)
Deployment of sewage water in agriculture offers an efficient way to conserve water, recycle the nutrients, reduce the pollution of surface water sources and to overcome the pressure on dwindling fresh water resources. But, constant monitoring is required to reduce the risks associated, and treatment of sewage water prior to use in crop production is also important.